Luteolin Modulates Neural Stem Cells Fate Determination: In vitro Study on Human Neural Stem Cells, and in vivo Study on LPS-Induced Depression Mice Model - Achour, Mariem; Ferdousi, Farhana; Sasaki, Kazunori; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2021)
Luteolin is a natural flavone with neurotrophic effects observed on different neuronal cell lines. however, its effects on human neural stem cells (hNSCs), and on pathological animal model with astrocytogenesis defect have not been investigated. We aimed to assess the effect of luteolin on hNSCs fate determination and on the inflammatory model of depression (LPS-induced depression mice) as a pathological animal model with astrocytogenesis defect. hNSCs were cultured in basal cell culture medium (control) or medium supplemented with luteolin or AICAR, a known inducer of astrogenesis. Transcriptomic analysis, immunocytochemistry, and quantitative gene expression was conducted on hNSCs. After depression induction by LPS injection, luteolin (10mg/Kg) was orally administrated to mice during 8 consecutive days. Behavioral, biochemical and transcriptomic analysis were performed. In hNSCs luteolin upregulated genes involved in neurotrophin, dopaminergic, hippo, and Wnt signaling pathways, and downregulated genes involved in p53, TNF, FOXO, and Notch signaling pathways suggesting the direction of hNSCs differentiation toward astrocytes by upregulation of GFAP and genes related to Wnt, BMP, and JAK-STAT signaling pathways. Luteolin downregulated the expression of TUBB3, NEUROD 1 and 6, and MBP suggesting its inhibitory effects on neurogenesis and oligodendrocyte genesis. Immunostaining showed that luteolin and AICAR significantly enhanced the differentiation of hNSCs into astrocytes. The RT-qPCR showed that luteolin specifically upregulated the expressions of GFAP, BMP2 and STAT3, whereas the expression of TUBB3 remain unchanged. In vivo, luteolin decreased the IL-6 production by astrocytes, decreased the serum levels of IL-6, TNFα, and corticosterone and it increased the levels of mature BDNF, dopamine, and noradrenaline levels in the hypothalamus of LPS induced depression mice. Transcriptomic results highlighted the modulatory effect of luteolin on different signaling pathways involved in the pathophysiology of depression and pointed out the anti-depressant effect of this flavonoid via the restoring effect exerted on NSCs signaling and the modulation of the stem cells fate to overcome the damage related to neurogenesis and astrogenesis processes caused by LPS injection. Luteolin may have enhanced astrogenesis in hNSCs exclusively via the BMP2-STAT3 pathway and it may exert a potential in vivo astrogenic effect through the modulation of WNT- JAK-STAT signaling